Two homological problems on skew PBW extensions arising in non commutative algebraic geometry (2016)
Abstract. In this work we study Auslander regularity conditions and the strongly noetherian property for the skew P BW extensions. The Cohen-Macaulay condition is also analyzed. In addition, as application of strongly noetherian algebras, we make an introduction to the non-commutative algebraic geometry of finitely graded algebras via its point modules.